Translational thoracolumbar injury after motor vehicle collision with uretero-thecal fistulization: a case report - Kapoor, Harit; Lee, James T.; Farag, Ahmed; Tucker, Brain; Pereira, Alex (Journal of Emergency and Critical Care Medicine, 2019)
Blunt torso trauma leading to translational thoracolumbar injury is a rare and serious injury requiring high amount of energy to produce this injury pattern. Translational thoracolumbar injuries have high association with spinal dural tears and traumatic aortic injuries however, associated traumatic ureteral injury is rare. This case report presents a unique combination of traumatic ureteral and dural injury resulting in an abnormal fistulous communication between the two, in a patient with translational thoracolumbar injury after motor vehicular collision. Unexpected “myelogram-like” appearance was seen with excreted urinary contrast mixing with the CSF in the spinal and intracranial subarachnoid spaces. No other reports of such a traumatic uretero-thecal fistula were found in our comprehensive search through the published English literature.